Guyana. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Guyana are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as good agricultural practices, exports, trade, beekeeping, hydroponics, employment of greenhouses, innovation, resilience against climate change, pest control, such as the fruit fly. Likewise, work was done on risk management, through risk maps, on water collection and on the effective management of this resource. Finally, training was provided to women to achieve their inclusion in agriculture.